The interplay between family and emigration from Romania - Bradatan, Cristina Elena (Migration Letters, 2014)
East European migration became a significant feature in the post 1990 Europe. Although migration based on family connections is the most frequently used form of legal entry into the European Union, and family structure influences (and it is influenced by) migration, in the European literature more attention has been paid to individual (labour) migration rather than family migration. This paper intends to be a review of studies on family migration from Romania. Through this study, ‘family migration’ is used to understand not only the migration of the whole family unit but also migration of individuals within the context of family